2017
DOI: 10.1007/978-3-319-45023-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Family Networks for Learning and Knowledge Creation in Developing Regions

Abstract: With the rise of the knowledge economy, learning and knowledge creation rather than material resources and assets are becoming competitive advantages of regions and countries. Unlike concrete inputs, which are produced mechanically, intangible knowledge is created through agents' interaction and communication, which are structured by social relations and norms within organizations, communities, and societies. Accordingly, knowledge-creating regions both in traditional sectors (e.g., the Third Italy) and high-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 39 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Any network always forms the way of gaining experiences. So, networks modify the way knowledge is constituted, and as we saw with Li (2017), they also promote specific ways of learning, differentiating e.g., contexts characterized more by family ties or by networks of friends. Anyway, concepts, ideas-knowledge-are on their way through networks.…”
Section: Consequences and Outlookmentioning
confidence: 90%
See 4 more Smart Citations
“…Any network always forms the way of gaining experiences. So, networks modify the way knowledge is constituted, and as we saw with Li (2017), they also promote specific ways of learning, differentiating e.g., contexts characterized more by family ties or by networks of friends. Anyway, concepts, ideas-knowledge-are on their way through networks.…”
Section: Consequences and Outlookmentioning
confidence: 90%
“…In general, family plays an important role in local economic learning processes in majority of world contexts. But contrary to the above, Li (2017) showed that families are extremely helpful to those local technological learning processes that require repeated communication and interaction. “In traditional communities family bridges can enable entrepreneurs to learn business and technical know‐how quickly” (Li, 2017, p. 80).…”
Section: Creativity and Innovations And The Impact Of Regions On The ...mentioning
confidence: 99%
See 3 more Smart Citations